The Correlation of Vocabulary Mastery and Effective Sentences With Exposition Writing Ability in Middle School Students - Sumaliyo, Sumaliyo; Alfiawati, Riska; Subari, Imam (IJLHE: International Journal of Language, Humanities, and Education, 2019)
This study aimed to determine and describe the correlation of vocabulary mastery and effective sentence mastery with the exposition writing ability in class VIII SMP Nusantara 2018/2019 academic year. The population and sample in this study were all Class VIII SMP Nusantara students. The quantitative research method determines the magnitude of the relationship between variables. There is still much inappropriate use of vocabulary, and the students' mastery of effective sentences is still lacking. The findings show: 1) vocabulary mastery has a significant relationship with the ability to write exposition with a correlation coefficient of 0.630, 2) effective sentence mastery has a significant relationship with the ability to write exposition with a correlation coefficient of 0.693, and 3) vocabulary mastery and Effective sentence mastery has a significant relationship together with the ability to write exposition with a correlation coefficient of 0.733.